STRATEGI OPTIMALISASI PENGALAMAN PELANGGAN DALAM MENINGKATKAN RETENSI PELANGGAN DI LEMBAGA PENDIDIKAN TINGGI: STUDI KASUS ITB STIKOM BALI KAMPUS JIMBARAN - Ni Wayan Sri Jayanti; I Made Pradipta; Kadek Ray Gangga Jyontika; I Putu Suarsujana Yoga Saputra; Dewa Gede Sutama Putra (Universitas KH. Abdul Chalim Mojokerto, 2026)
Competition among higher education institutions in Indonesia demands that educational organizations deliver superior learning experiences to maintain student retention. This study aims to analyze the influence of academic service quality, administrative support, campus facilities, and social interaction on student retention at ITB STIKOM Bali Jimbaran Campus. The research employs a mixed-methods approach with a sequential explanatory design, involving 250 active students from the odd semester of 2025/2026 across four study programs. Quantitative data were collected through questionnaires and analyzed using multiple linear regression, while qualitative data were obtained through in-depth interviews to strengthen empirical findings. Results indicate that all four variables significantly and positively influence student retention both partially and simultaneously, contributing 89.5 percent of the variance. Administrative support demonstrates the strongest influence, followed by academic service quality, social interaction, and campus facilities. These findings confirm that holistic customer experience, encompassing academic, administrative, facility, and social aspects, serves as a key determinant in enhancing student retention. This research contributes to the development of a customer experience model within the Indonesian higher education context and provides practical implications for higher education managers in designing comprehensive and sustainable retention strategies based on student experience.